2021
DOI: 10.1093/femsec/fiab080
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of two highly insecticidal, endophytic strains of Bacillus thuringiensis

Abstract: Recent discovery of endophytic strains of Bacillus thuringiensis significantly improves the knowledge on its ecology. It also may be a new source for the isolation of insecticidal strains. This report shows the characterization of two endophytic, highly insecticidal strains of B. thuringiensis. Strains LBIT-1250L and LBIT-1251P were isolated from lavender and Poinsettia sap, respectively. Their parasporal crystals were very similar in morphology to those shown by serotypes israelensis and kurstaki, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…However, the toxicity of Bt acting as an endophyte/rhizospheric bacterium is not well characterized. The toxicity results reported to date of Bt associated with plants, corroborate that Bt can be toxic to different kinds of phytopathogens (fungi, bacteria, viruses and oomycetes) and predators (insects, nematodes) 15,16,18,31–38,40,41,43–48,65 (Fig. 1).…”
Section: Toxicity Of Bacillus Thuringiensis Isolates With Endophyte/r...supporting
confidence: 63%
See 4 more Smart Citations
“…However, the toxicity of Bt acting as an endophyte/rhizospheric bacterium is not well characterized. The toxicity results reported to date of Bt associated with plants, corroborate that Bt can be toxic to different kinds of phytopathogens (fungi, bacteria, viruses and oomycetes) and predators (insects, nematodes) 15,16,18,31–38,40,41,43–48,65 (Fig. 1).…”
Section: Toxicity Of Bacillus Thuringiensis Isolates With Endophyte/r...supporting
confidence: 63%
“…Few reports are published that provide toxicity of isolated Bt strains from the plants naturally colonized 39,41 or artificially inoculated 5,40 with Bt isolates. To date, three studies 5,39,41 have reported toxicity of Bt isolated from colonized (natural 39 and artificial 5,41 bacterial colonization) plants of cotton, lavender, poinsettia and Arabidopsis thaliana . Monnerat et al 39 .…”
Section: Toxicity Of Bacillus Thuringiensis Isolates With Endophyte/r...mentioning
confidence: 99%
See 3 more Smart Citations